Sustainable Aviation Fuels : Status, challenges and prospects of drop-in liquid fuels, hydrogen and electrification in aviation. Issue 3 (1st July 2020) - Bauen, Ausilio; Bitossi, Niccolò; German, Lizzie; Harris, Anisha; Leow, Khangzhen
Aviation fuel demand is expected to continue to grow over the next decades and continue to rely heavily on kerosene fuel for use in jet engines. While efficiency and operational improvements are possible ways to reduce greenhouse gas (GHG) emissions, decarbonisation will need to heavily rely on low carbon kerosene drop-in alternatives. Currently, alternative fuels make up a very small share of fuel used in aviation, but their commercialisation is making good progress. Hydrogen offers a longer-term alternative fuel option but requires aircraft design and fuelling infrastructure changes. Electrification is emerging as an option for providing propulsion in aircraft, either in pure form in small aircraft or in hybrid mode in larger aircraft. This paper reviews the status, challenges and prospects of alternative fuels and electrification in aviation.